Sex and the Nazi soldier : violent, commercial and consensual encounters during the war in the Soviet Union, 1941-45 - Mühlhäuser, Regina (Advances in critical military studies., 2021)
Sexual violence was a widespread reality during the war and the occupation in the Soviet Union: Wehrmacht soldiers and SS men made women and girls victims of sexual torture, committed rape and sexual enslavement. They also visited both 'secret' prostitutes and official military brothels, and had encounters with women who were forced to trade sex for protection or food. In some areas, they engaged in consensual relations, which sometimes led to applications for marriage permits.--